Tunable Channel Drop Filter using Hexagonal Photonic Crystal Ring Resonators - Mohammad Reza Rakhshani; MohammadAli MansouriBirjandi (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
In this paper, we have proposed a tunable two dimensional (2D) photonic crystal (PhC) channel drop filter (CDF) using ring resonators with suitable quality factor (Q) and transmission efficiency; we investigate parameters which have an effect on resonant wavelength in this CDF, such as dielectric constant of inner, coupling, adjacent and whole rods of the structure. Dropping efficiency at the resonance and quality factor of single ring are 90% and 1046, respectively. The footprint of the proposed structure is about 125.6μm2; therefore this structure can be used in the future photonic integrated circuits. DOI: http://dx.doi.org/10.11591/telkomnika.v11i1.1788